Husband's knowledge and perception on iron consumption compliance among pregnant women in Hospital Universiti Sains Malaysia - Saidon, Norelysya Nabila (Universiti Sains Malaysia, 2024)
Anemia is a major global problem in public health that particularly affects individuals in various stages of life, including young children, and adolescent girls experiencing menstruation, as well as pregnant and postpartum women. The study aims to assess the level of husband's knowledge and perception on iron consumption compliance among pregnant women in Hospital Universiti Sains Malaysia (HUSM). A cross-sectional study was conducted on husband of pregnant women in Obstetrics and Gynecology (O&G) clinic and obstetrics ward at HUSM. Data was collected using a self-administered questionnaire. 125 husband of pregnat women who fulfilled the inclusion criteria of this study was selected to answer the questionnaire. They were selected through convenience sampling. The study used descriptive statistics and Pearson Chi-square. The results show that 116 (92.8%) participants had a high knowledge level on iron consumption compliance among pregnant women and 71 (56.8%) of the participants have poor level of perception on iron consumption compliance among pregnant women. There was no association between knowledge score and perception score (p = 0.786), the result shows only 65(91.5) of participants have good knowledge with a negative perception on iron consumption compliance in pregnant women. In conclusion, this study may contribute to enhancing the husband's role in encouraging pregnant women to take iron supplements regularly. However, further research should involve a larger sample of pregnant women's husbands from various hospitals across different districts to provide more accurate and representative findings.